If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -1t = 5 + 2t Solving 2 + -1t = 5 + 2t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-2t' to each side of the equation. 2 + -1t + -2t = 5 + 2t + -2t Combine like terms: -1t + -2t = -3t 2 + -3t = 5 + 2t + -2t Combine like terms: 2t + -2t = 0 2 + -3t = 5 + 0 2 + -3t = 5 Add '-2' to each side of the equation. 2 + -2 + -3t = 5 + -2 Combine like terms: 2 + -2 = 0 0 + -3t = 5 + -2 -3t = 5 + -2 Combine like terms: 5 + -2 = 3 -3t = 3 Divide each side by '-3'. t = -1 Simplifying t = -1
| 17x^2-24xy=0 | | -1+3x=2x+11 | | 7-16-(-3-4)= | | -17+10-61-(-3)= | | 2(x+1)=2(x+3) | | (4x-1)^1/2=6 | | -16+10-61-(-3)= | | (5y+7)-(4+4y)=9 | | 3n^2-20n=-32 | | 10-5b=110 | | 2/3r=6 | | 8x+44=12x | | q/4+7=5 | | 2.4+(-3.7)= | | -3.8-2.9= | | -9-9-9-9= | | -60-(-8-3)= | | -9=-7+2y | | 12(12q+4)= | | 12-(1-5)= | | 45x+27y=1750 | | 26=4-u+2 | | 9-13-(-44)= | | -5(5x-7)+4=-25x+39 | | 36x^2-24x+4=0 | | h=3vt+19t^2 | | 9-13-(44)= | | 2(72+71b+7b^2)= | | 5x-8=3x-16 | | 4t+5+5t-8t=5+6 | | 4+7-20= | | 18-(-15)-2= |